Effect Of Emotional Freedom Technique On Pre Percutaneous Coronary Intervention Patients' Anxiety In Hospital - Syara, Arfah May; Gandaria Purba, Anita Sri; Harefa, Karnirius (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Coronary heart disease is a degenerative disease. One of the techniques that can open blood vessels and return blood through the coronary arteries is Percutaneous Coronary Intervention (PCI). Hemodynamic conditions are one of the patient's preparations for PCI, but anxiety can respond to the cardiovascular system, one of which is a disturbance in a person's hemodynamics. Problems that often arise in pre PCI patients are anxiety.Percutaneous Coronary Intervention is one of the techniques that have been invented to open the blood vessels and return blood through the coronary arteries (PCI). PCI, also known as cardiac catheterization, is a procedure that involves inserting one or more catheters into the heart and blood arteries. The catheter is inserted through a peripheral vessel, usually femoral, then non-operatively invasive so that complications can be kept as low as possible. Percutaneous Coronary Intervention (PCI) can cause complications in the form of myocardial infarction, stroke, arrhythmia and death. This causes a person to feel himself threatened, someone feels himself threatened can cause the effect of Anxiety (anxiety). The problem that often arises in pre PCI patients is anxiety. One of the efforts to overcome anxiety is the Emotional Freedom Technique (EFT). This type of research is a quantitative study using a quasi-experimental design with a pretest-posttest with a control group, namely by conducting a pretest in both groups and followed by an intervention in the experimental group and then conducting a posttest in both groups, with a sample of 34 respondents. The results showed that the effect of EFT on the anxiety of pre PCI patients in the intervention group with p-value = 0.000, while in the control group with p-value = 0.650. Furthermore, it is hoped that clients who will undergo PCI will not be hindered from doing PCI because the client has been given Emotional Freedom Technique (EFT) therapy.